1993
DOI: 10.1136/jnnp.56.11.1207
|View full text |Cite
|
Sign up to set email alerts
|

Delirium associated with Joseph disease.

Abstract: Three Japanese patients with Joseph disease from different families developed sleep disturbance, followed by delirium at the middle to end stage. Brain CT scans of the three patients showed brainstem tegmental atrophy. EEG revealed slowing of background activity. Two necropsy cases showed degeneration of the reticular formation, raphe nuclei and locus ceruleus in the brainstem tegmentum in addition to the common pathological findings of Joseph disease. The clinicopathological correlation between the delirium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Cognitive decline is not a feature of typical MJD, however 9. In another interesting case, the offspring of a consanguineous marriage, with psychotic behavior and dementia, had possible MJD with possible RBD 10. His CAG repeat numbers were 60 & 60, which is higher than normal but smaller than required for a genetic diagnosis of MJD.…”
Section: Discussionmentioning
confidence: 97%
“…Cognitive decline is not a feature of typical MJD, however 9. In another interesting case, the offspring of a consanguineous marriage, with psychotic behavior and dementia, had possible MJD with possible RBD 10. His CAG repeat numbers were 60 & 60, which is higher than normal but smaller than required for a genetic diagnosis of MJD.…”
Section: Discussionmentioning
confidence: 97%
“…A few investigators, mainly from Japan, have reported that prominent psychiatric symptoms, as well as sleep disturbance, are associated with this condition. We found 11 such patients (including ours) from the literature (Ishino et al ., 1971; Ikeda, 1987; Fukutani et al ., 1993; Kushida et al ., 1995; Inui et al ., 2000; Mizoguchi et al ., 2000; Takama et al ., 2000). MJD was diagnosed clinicopathologically for six and for five by molecular genetics.…”
Section: Discussionmentioning
confidence: 99%
“…This report is the first of SCA 3 being associated with RBD‐like symptoms. There are two publications describing peculiar sleep behavior in SCA 39, 10 that does not fit the RBD syndrome. In one case, the patient had episodes lasting several minutes during both non‐REM as well as REM sleep,9 whereas in the other, 3 patients had delirium starting in but persisting after sleep 10.…”
Section: Neurodegenerative Disorders Associated With Rbdmentioning
confidence: 99%
“…There are two publications describing peculiar sleep behavior in SCA 39, 10 that does not fit the RBD syndrome. In one case, the patient had episodes lasting several minutes during both non‐REM as well as REM sleep,9 whereas in the other, 3 patients had delirium starting in but persisting after sleep 10. These 3 unrelated patients all were demented, a problem not reported in other SCA 3 families 10.…”
Section: Neurodegenerative Disorders Associated With Rbdmentioning
confidence: 99%
See 1 more Smart Citation